La Obra de Arte en la Época de su Hiperreproducibilidad Digital - Cuadra Rojas , Álvaro (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
This article aims to examine the Benjaminian notion of reproductibility in the conditions generated by the expansion of digital technologies in the age of hypermodernity. More than a study of Walter Benjamin, himself this is an essay inspired by the heuristics and the 'correspondences' implicit in the work of the great thinker of the Frankfurt School thinker with a view to interrogating the present moment of planetary culture, as pervaded day-to-day by the new mnemotechnologies.
Keywords: Hyperreproduction; art; flux; digital; media